2014
DOI: 10.1007/s11307-014-0793-5
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of [18F]-labelled Maltose Derivatives as PET Tracers for Imaging Bacterial Infection

Abstract: Purpose To develop novel positron emission tomography (PET) agents for visualization and therapy monitoring of bacterial infections. Procedures It is known that maltose and maltodextrins are energy sources for bacteria. Hence, 18F-labelled maltose derivatives could be a valuable tool for imaging bacterial infections. We have developed methods to synthesize 4-O-(α-D-glucopyranosyl)-6-deoxy-6-[18F]fluoro-D-glucopyranoside (6-[18F]fluoromaltose) and 4-O-(α-D-glucopyranosyl)-1-deoxy-1-[18F]fluoro-D-glucopyranosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 24 publications
0
39
0
2
Order By: Relevance
“…It has been known that enterobacteriacease express the enzyme sorbitol‐6‐phosphate dehydrogenase which is responsible for sorbitol metabolism. We showed the use of 6‐[ 18 F]fluoromaltose, and Ning et al reported the application of 18 F‐ labeled fluoromaltohexose as PET probes targeting the bacterial maltodextrin transporter, to image all bacterial infections caused by both Gram positive and Gram negative bacteria. Both of these tracers demonstrated great specificity for distinguishing bacterial infection from inflammation but had poor signal to noise ratios due to possible metabolism in the hepatobiliary system.…”
Section: Introductionmentioning
confidence: 99%
“…It has been known that enterobacteriacease express the enzyme sorbitol‐6‐phosphate dehydrogenase which is responsible for sorbitol metabolism. We showed the use of 6‐[ 18 F]fluoromaltose, and Ning et al reported the application of 18 F‐ labeled fluoromaltohexose as PET probes targeting the bacterial maltodextrin transporter, to image all bacterial infections caused by both Gram positive and Gram negative bacteria. Both of these tracers demonstrated great specificity for distinguishing bacterial infection from inflammation but had poor signal to noise ratios due to possible metabolism in the hepatobiliary system.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously demonstrated the development of 6-18 F-fluoromaltose (Supplemental Fig. 1; supplemental materials are available at http://jnm.snmjournals.org), a probe from a novel class of tracers targeting the maltodextrin transporter in bacteria (14,15). The concept of this class of tracers stems from an earlier study by Murthy et al, who showed that the maltodextrin transporter is unique to bacteria and that a fluorescently labeled maltohexose probe was able to image E. coli-induced myositis in rats (16).…”
mentioning
confidence: 99%
“…7) kann mittels nukleophieler Substitution von entsprechenden Precursoren synthetisiert werden. Die derzeit erzielbaren Ausbeuten sind bislang gering [102]. 6-[ 18 F]Fluormaltose reichert sich in unterschiedlichen Bakterienkulturen an.…”
Section: Visualisierung Des Bakteriellen Metabolismusunclassified